Impact of Vestibular Rehabilitation and Dual‐Task Training on Balance and Gait in Survivors of Stroke: A Systematic Review and Meta‐Analysis - Brooke Nairn; Nehzat Koohi; Diego Kaski; Doris‐Eva Bamiou; Marousa Pavlou (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Evidence supports that vestibular rehabilitation therapy (VRT) improves the static and dynamic balance of survivors of stroke, yet VRT is rarely included in stroke rehabilitation guidelines. We aim to answer the question: What are the effects of VRT or dual‐task training (DTT) on balance and gait for reducing the risk of falls among survivors of late subacute and chronic stroke? Methods Following the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis Statement guidelines, electronic databases PubMed, EMBASE, MEDLINE, Web of Science, and Scopus for English were searched to identify randomized controlled trials published within the past 10 years in the English language, investigating VRT for patients with late subacute and chronic stroke. Results Eleven studies (n=509 participants) were included in the systematic review, and 10 studies (n=413 participants) were included in a meta‐analysis. The average participant age was 60.9 years, with 62.11% male. On average, 36 months had passed since stroke onset. The pooled effect standardized mean difference suggests that VRT has a significantly large effect for improving balance (standardized mean difference, 0.64 [95% CI, 0.44–0.85], P<0.00001), particularly from balance‐specific training (standardized mean difference, 1.07 [95% CI, 0.70–1.45], P=0.002). Dual‐task training (DTT) moderately improved gait (standardized mean difference, 0.46 [95% CI, 0.18–0.74], P=0.001), with greater benefits from DTT compared with single‐task training. Conclusions Despite substantial heterogeneity across studies, the evidence supports that VRT, can probably improve balance, and DTT may improve gait outcomes among survivors of late subacute and chronic stroke. An optimal program for this population should focus on balance and DTT with subcomponents of gait and strength training. Further research is required to determine the optimal number of weeks, sessions/week, and duration (minutes) of VRT sessions. Registration URL:  https://www.crd.york.ac.uk/PROSPERO/; Unique identifier: CRD42023450254.